GOOGLE CLOUD ASSOCIATE CLOUD ENGINEER CERTIFICATION AND AND IMPLEMENTATION GUIDE master the deployment, management, and monitoring of Google Cloud solutions - Koziorowska, Agnieszka; Marusiak, Wojciech (Packt Publishing Ltd., 2023)
Gain practical knowledge and hands-on expertise in implementing Google Cloud Platform services and prepare to confidently pass the exam on your first attempt Key Features Explore Google Cloud Platform services and operations in depth Gain hands-on experience to effectively employ Google Cloud services Receive tailored guidance for Associate Cloud Engineer certification from Google experts Purchase of the print or Kindle book includes a free PDF eBook Book Description Google Cloud Platform (GCP) is a leading cloud provider, helping companies and users worldwide to solve the most challenging business issues. This book will teach cloud engineers working with GCP how to implement, configure, and secure cloud environment, and help students gain confidence in utilizing various GCP services. The book begins by introducing you to Google Cloud and the ACE exam, including various resources that can help you pass. The next set of chapters will help you explore the various compute options in Google Cloud, such as Google Kubernetes Engine and Google Compute Engine. As you advance, you'll gain a clear understanding of the essence of the cloud, including networking and storage, as well as the data analytics products that Google Cloud provides. The chapters also cover key topics such as monitoring, logging, diagnostics, and price estimation along with the most crucial of subjects, security, with a particular focus on identity and access management. Finally, you'll be given the chance to test your newfound knowledge with the help of two mock exams. By the end of this book, you'll have learned the difference between various Google Cloud Platform services, along with specific use cases, and be able to implement these services with the GCP console and command-line utilities. What you will learn Grasp the key topics needed to achieve ACE certification Import and export data to and from Google Cloud Implement and configure various networking options in Google Cloud Derive insights from data with Google Data Analytics Gain knowledge and experience in monitoring and logging Test yourself in various scenarios while reading the book Choose the optimal options to manage your solution's data Who this book is for This book is for anyone preparing for Associate Cloud Engineer certification. It can be used by IT system administrators as well as DevOps and it will be most useful to cloud architects as it covers all areas of Google Cloud Platform. This guide is ideal for those who want to start working with Google Cloud, gain practical knowledge, and achieve certification.